IMPROVING STUDENTS’ READING COMPREHENSION ON RECOUNT TEXT BY USING SQ4R AND MEDIA BOOKLET - Hananiel, .; Sada, Clarry; Novita, Dewi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2015)
Abstrak: Sebagian besar siswa kelas sembilan SMPN 1 Sungai Betung kurang mampu dalam mencari arti kata-kata dan menyebutkan informasi detail (karakteristik, pengaturan dan tema) dari struktur generik teks recount yang terdiri dari orientasi, komplikasi, dan resolusi. Oleh karena itu penerapan metode SQ4R dan Booklet akan membantu mereka dalam mengetahui arti kata memahami informasi dari struktur generik teks dengan mudah. Metode penelitian ini merupakan penelitian tindakan kelas yang diterapkan pada 25 siswa kelas 9C SMPN 1 Sungai Betung. Pengumpulan datanya melalui test tertulis seperti pilihan ganda, isian dan catatan selama pengamatan. Hasil pada siklus pertama belum memuaskan yaitu 61,20, sedangkan pada siklus kedua hasilnya sangat memuaskan yaitu 86,40. Kata kunci: Pemahaman Bacaan Teks Recount, metode SQ4R dan Media Booklet Abstract: Most of the ninth grade students of SMPN 1 Sungai Betung was poor in their vocabulary mastering especially finding the meaning of words. They were also poor in their ability in mentioning the detail information (characteristic, setting and theme) from recount text. With this problems the teacher tried to use other tecnique and media of teaching to improve students ability. Therefore, the application of SQ4R methods and booklet was used to help them to know the meaning of words to understand detail information of the generic structure of text with easier. This research method is a classroom action research that was applied to the 25 students of class 9C SMPN 1 Sungai Betung. Data collection through written test such as multiple choice, stuffing and notes during the observation. The results of the study was that the students’ progress during teaching and learning activity in Cycle 1 and Cycle 2. In Cycle 1 mean score  was 61.20, and in Cycle 2 the students’ improved significantly become  86.40. Keywords: Reading Comprehension, SQ4R methods and media Booklet.